Self-regulated learning in online classes: A comparative study between Malaysian and Indonesian students - Anas Bin Tajudin; Chusna Maulida; Ria Dwi Vransiska (UIN Raden Mas Said Surakarta, 2022)
Self-regulated learning (SRL) becomes a crucial part for the success of online classroom activities during the COVID-19 pandemic. To date, studies exploring students’ SRL in the contexts of Malaysian and Indonesian universities are still lacking and remain more empirical evidence. This study aims to examine and compare both university students’ SRL toward online learning activities at the time of global pandemic. The required data are quantitatively collected from 103 undergraduates from University A in Malaysia and 119 college students from University B in Indonesia by using an online questionnaire on students’ self-regulated learning adapted from Motivated Strategies for Learning Questionnaire (MSLQ). The sudden shifting from face-to-face interaction to online class instruction is a new learning style and could be challenging, but the finding of this study shows that the students from both universities achieve high mean scores on the SRL questionnaire. This finding indicates that the students have a positive attitude, high academic motivation levels, and good self-learning control over themselves during the online classes. This study contributes to the extension of the current literature about self-regulated learning in higher education context. This study further suggests that teachers could assist students’ self-regulated learning to improve their academic performances by keeping their motivation and engagement, particularly in the time of online classes during COVID-19 pandemic era. Hence, future studies are recommended to investigate the impact of students’ SRL on learning achievement as it can help teachers to enhance students’ performance in online classes.